Different methods of managing bluestem pastures - Smith, E.F.; Anderson, K.L.; Koch, B.A.; Walker, G.L.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Two-year-old Hereford steers with an average USDA feeder grade of High Good were used to stock the pastures. They had been purchased as calves from near Melrose, N.M., and had been used in this study as yearlings during the summer of 1957. During the winter of 1957-58 they were wintered on bluestem pasture and supplemented with about 2 pounds of soybean pellet per head daily until mid-January and were then moved to drylot and fed prairie hay with about 4 pounds of alfalfa hay per head daily. This ration was continued until May 1, 1958.
Keywords: Beef; Bluestem pasture; Gains; Stocking rate